IMPROVING NATURAL SCIENCE LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING MODELS IN FIFTH-GRADE SDN 1 KURNIA MATARAM - Waziana, Winia; Ponidi, Ponidi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
Teachers must have creativity in using learning models so that students can actively participate as learning centers. Creativity and learning innovation carried out by teachers can increase students' interest in learning. Students as educational subjects are required to be active in learning to find information and explore alone or in groups. The teacher only acts as a facilitator and guide towards optimizing the achievement of the knowledge learned. Classroom action research was conducted because the researcher wanted to improve the learning outcomes of fifth-grade students at SDN 1 Kurnia Mataram in science subjects by applying cooperative learning methods. This is because the learning model used is still using the old method which is considered less attractive to students. This research is a classroom action research with the research subject of class V students of SDN 1 Kurnia Mataram, totaling 25 students and the object of research is the result of learning science. Data were collected by using observation, documentation, and test methods by applying two cycles. Further processed using quantitative descriptive analysis techniques. The results of this study showed an increase in the value of student learning outcomes. The average value of the initial condition test was only 62.60 with learning completeness only reaching 24.00% after the cooperative learning method was applied. The average student score in the first cycle was 64.20 with learning mastery reaching 36.00%. While in the second cycle the average value reached 76.59 with learning completeness reaching 84.00%.